2007
DOI: 10.1159/000099585
|View full text |Cite
|
Sign up to set email alerts
|

CD4<sup>+</sup>CD25<sup>high</sup> Regulatory T Cells Are Markedly Decreased in Blood of Patients with Pemphigus Vulgaris

Abstract: Background: It remains to be determined whether pemphigus vulgaris (PV), an autoimmune blistering disease, has a reduction and/or dysfunction of CD4+CD25high regulatory T (Treg) cells. Objectives: To evaluate the frequency and phenotypes of Treg cells in blood of patients with PV. Methods: Peripheral blood mononuclear cells were prepared from PV patients as well as normal and disease control volunteers, and the frequency and phenotypes of Treg cells were determined by flow cytometry. CD4<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 93 publications
(85 reference statements)
3
39
1
5
Order By: Relevance
“…Taken together, the CD4+ CD25bright-FOXP3+ cells shown to be reduced in BP patients exhibited the Tregs characteristic phenotypic features. The Treg phenotypic modulation shown by our study in BP patients is similar to that reported in PV patients where a reduction in circulating Tregs and a preferential CCR4 and CD62L expression on the CD4+ CD25bright cells were reported [31].…”
Section: Discussionsupporting
confidence: 90%
“…Taken together, the CD4+ CD25bright-FOXP3+ cells shown to be reduced in BP patients exhibited the Tregs characteristic phenotypic features. The Treg phenotypic modulation shown by our study in BP patients is similar to that reported in PV patients where a reduction in circulating Tregs and a preferential CCR4 and CD62L expression on the CD4+ CD25bright cells were reported [31].…”
Section: Discussionsupporting
confidence: 90%
“…An earlier study demonstrated a decrease in Treg cells in the blood of pemphigus patients [57], while another showed increased Treg cells from patient lesional biopsy specimens [56]. It is possible that this discrepancy is reflective of the regulatory cells migrating from the blood to the skin lesions and regional lymph nodes.…”
Section: Tregmentioning
confidence: 99%
“…It has been postulated that active immune suppression operates in healthy individuals possessing Dsg 1- and Dsg 3-reactive T cells, and that an imbalance of the putative relationship between autoreactive Th and Tregs (Tr1) cells is critical to the development of pemphigus [159]. In support, the CD4 + CD25 + hi Tregs are decreased in peripheral blood of PV patients [160]. Furthermore, a subset of Dsg 3-reactive, interleukin (IL)-10-secreting Tr1 cells was found in the majority of healthy carriers of PV-associated HLA class II alleles and only in <20% of PV patients [161].…”
Section: Regulation Of Pemphigus Autoimmunitymentioning
confidence: 99%